2014
DOI: 10.5336/medsci.2013-36830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polysomnography Variables in Obstructive Sleep Apnea Patients with or without Excessive Daytime Sleepiness

Abstract: A AB BS S T TR RA AC CT T OOb b j je ec c t ti i v ve e: : Excessive daytime sleepiness (EDS) is a common symptom in patients with obstructive sleep apnea (OSA), and the reason for this could not be fully elucidated. The aim of this study was to compare polysomnographic and demographic features of patients with OSA with or without EDS according to Epworth Sleepiness Scale (ESS). M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : A total of 82 adult patients who were diagnosed with OSA with polysomnogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous studies that examined the correlation between sleep study parameters and ESS showed an association between hypoxemia, BMI, and AHI to EDS [ 7 , 20 22 ]. Another study, by Gulbar et al, showed significant correlation between the duration of sleep apnea/hypopnea and EDS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that examined the correlation between sleep study parameters and ESS showed an association between hypoxemia, BMI, and AHI to EDS [ 7 , 20 22 ]. Another study, by Gulbar et al, showed significant correlation between the duration of sleep apnea/hypopnea and EDS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%